The Impassioned Life : Reason and Emotion in the Christian Tradition - Powell, Samuel M. (Book collections on Project MUSE., 2016)
The Impassioned Life argues that theology's task today is to rethink the nature of the emotions and their relation to human reason. Such rethinking is necessary because the Christian tradition feels ambivalently about the emotions. Armed with a commitment to body-soul dualism, many writers have equated the image of God with rationality and wondered whether emotion is an essential feature of human nature; however, the tradition has also affirmed the value of emotions such as love and compassion and has sometimes asserted the value of so-called negative emotions such as anger. The question, then, is whether the tradition's pastoral insight into the importance of moderation and control of the emotions requires us to think dualistically about soul (identified with reason) and body (the seat of emotions). To answer this question, The Impassioned Life explores the vital resources of the Christian theological tradition and also of contemporary scientific and psychological research in order to achieve a more adequate theological understanding of the emotions and reason. At heart, it offers a holistic, integrated vision of the Christian life lived passionately in its full range of human feeling as life in the Spirit.